A plasma metabolomics study suggests alteration of multiple metabolic pathways in patients with bipolar disorder. (May 2021) - Wei, Jinxue; Zhao, Liansheng; Du, Yue; Tian, Yang; Ni, Peiyan; Ni, Rongjun; Wang, Yingcheng; Ma, Xiaohong; Hu, Xun; Li, Tao
Highlights: Plasma metabolome was analyzed in patients with bipolar disorder and in healthy controls. Multivariate feature selection was used for identification of metabolites that could discriminate between patients and controls. Metabolite set enrichment analysis were used to identify the relevant biological pathways. Eighty metabolites could discriminate patients with bipolar disorder from healthy controls. Nine metabolic pathways were altered in the bipolar disorder patients. Abstract: Previous omics studies have greatly contributed to our knowledge of bipolar disorder. Metabolomics is a relatively new field of omics science that can provide complementary insight into data obtained from genomics, transcriptomics or proteomics analyses. In this study, we aimed to identify metabolic pathways associated with bipolar disorder. We performed a liquid chromatography-mass spectrometry-based study to identify plasma metabolic profiles in patients with bipolar disorder (N = 91) and healthy controls (N = 92). Multivariate features selection by sparse partial least square-discriminant analysis combined with metabolite set enrichment analysis were used to identify metabolites and biological pathways that discriminate patients with bipolar disorder from healthy controls. The results showed that eighty metabolites in the plasma were identified to discriminate patients with bipolar disorder from healthy controls, and nine metabolic pathways, i.e., (1) glycine and serine metabolism, (2) glutamate metabolism, (3) arginine and proline metabolism, (4) tyrosine metabolism, (5) catecholamine biosynthesis, (6) purine metabolism, (7) amino sugar metabolism, (8) ammonia recycling, and (9) carnitine synthesis, were identified to be altered in bipolar disorder compared to healthy controls. We conclude that the 80 metabolites and nine metabolic pathways identified might serve as biomarkers to distinguish bipolar disorder patients from healthy controls.